Seed‐based test–retest reliability of resting state functional magnetic resonance imaging at 3T and 7T. Issue 10 (14th September 2021) - Nemani, Ajay; Lowe, Mark J.
Abstract: Purpose: Ultrahigh field (UHF) resting state functional magnetic resonance imaging (rsfMRI) has become increasingly available for clinical and basic research, bringing improvements in resolution and contrast over standard high field imaging. Despite these improvements, UHF connectivity studies present several challenges, including increased sensitivity to physiological confounds and a vastly increased data burden. We present a direct quantitative assessment of test–retest reliability of functional connectivity in several standard functional networks between subjects scanned at 3T and 7T. Methods: Five healthy subjects were scanned over four sessions each in a scan‐rescan design at both 3T and 7T field strengths. Resting state fMRI data were segmented into four major intrinsic connectivity networks, and seed‐based peak correlations within and between these networks examined. The reliability of these correlations was assessed using intra‐class correlation coefficients (ICC). Results: Across all data, over 4000 peak correlations were extracted for assessment. The reliability over all intrinsic networks was greater at 7T than 3T (median ICC 0.40 vs. 0.33, p ≤ 0.0014), with each network individually showing improvement. Inter‐network reliability was stronger than intra‐network reliability, but intra‐network reliability showed the greatest improvement between field strengths. Conclusion: We demonstrate significantly increased reliability of resting state connectivity at UHF strengths over conventional field strengths using a novel hybrid seed‐based analysis. This result adds to the growing body of work supporting the migration of functional imaging studies to UHFs.